Impact of the use of social networking sites on job performance: effect of digital competence - Luz María Moyano-Castolo; Karla Barajas-Portas; Jorge Alberto Hidalgo-Toledo (Tourism & Management Studies)
This research examines the role that digital competence and the use of social networking sites (SNS) play in the workplace, focusing on female executives in the tourism sector. It analyzes the intersection between digital culture, technological innovation and its application in professional and everyday contexts. Despite the predominance of women in the sector, persistent gender gaps are observed in the workplace. It is argued that the domain of digital skills can act as a catalyst to mitigate these inequalities. The article offers an enriched definition of digital competence and examines its impact on job performance while addressing the risks and guidelines associated with the use of socio-digital networks. An analytical model is proposed to assess the job performance of female executives in tourism, focusing on digital technology and knowledge transfer. The results indicate a positive correlation between the versatile use of socio-digital networks and job performance. The importance of digital competence in the contemporary era is highlighted, and its implications for organizational culture, job satisfaction, academic performance and employee retention are discussed.